2000
DOI: 10.1159/000030143
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of Tumor Markers for Early Detection of Recurrence in Patients with Cervical Adenocarcinoma and Adenosquamous Carcinoma

Abstract: Objective: The clinical value of tumor markers for early detection of recurrence was investigated in 32 patients with cervical adenocarcinoma or adenosquamous carcinoma who had recurrent tumors. Methods: Serum levels of CA 125, CA 19-9, carcinoembryonic antigen (CEA), and squamous cell carcinoma antigen (SCC), in addition to clinical status at the time of recurrence were investigated. Results: Among the 32 patients, 26 had no symptoms at the time of recurrence. In 20 patients, elevated serum levels of tumor ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…The purpose of the new markers is primarily to reduce the percentage of undiagnosed patients, which will also improve their survival rate. Cytological screening proves successful for squamous lesions [2, 80] however this method is not effective in diagnostics of cervical adenocarcinoma yet [40]. Moreover, the cervical adenocarcinoma seems to be aggressive, and more often, lymph nodes metastases are observed in these patients [1].…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of the new markers is primarily to reduce the percentage of undiagnosed patients, which will also improve their survival rate. Cytological screening proves successful for squamous lesions [2, 80] however this method is not effective in diagnostics of cervical adenocarcinoma yet [40]. Moreover, the cervical adenocarcinoma seems to be aggressive, and more often, lymph nodes metastases are observed in these patients [1].…”
Section: Discussionmentioning
confidence: 99%
“…In the series of Leminen [88], CA 125 and CEA levels increased in 71 and 36%, respectively, of cervical adenocarcinoma patients who developed progressive disease. Tabata et al [91] detected elevated levels of CA 125, CA 19-9, CEA, CA 19-9 and/or CEA in 14, 62, 29 and 71% of 21 patients with recurrent adenocarcinoma and, respectively, in 37, 46, 64 and 100% of 11 patients with recurrent adeno-squamous carcinoma of the uterine cervix.…”
Section: Serum Ca125 Assay In the Monitoring Of Response To Treatmentmentioning
confidence: 96%
“…Among these latter, the logistic regression showed that pre-operative serum CA 125 > 26 U/ml was related to lymph-vascular space invasion (p = 0.04) and deep cervical stromal invasion (p = 0.002). Patients with cervical adenocarcinoma sometimes showed raised levels of 28,89,91] and CEA [33,85,86,88,89,91,92], first identified in tissue and serum samples from patients with colon cancer.…”
Section: Incidence Of Elevated Pre-treatment Serum Ca125 Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…CEA może być także wytwarzany i uwalniany do krążenia u chorych na nowotwory o innych umiejscowieniach, między innymi w nowotworach narządu rodnego, żołądka, trzustki, piersi, płuca, pęcherza moczowego, gruczołu krokowego oraz w przerzutach do wątroby [6,[23][24][25]. W piśmiennictwie opisywany jest związek stężeń CEA z typem histopatologicznym raka, w rakach gruczołowych szyjki macicy podwyższone stężenia CEA obserwuje się częściej niż w płaskonabłonkowych [10,16,26]. [5,10,23,27].…”
Section: Antygen Karcinoembrionalny (Cea)unclassified